The environments of Australopithecus anamensis at Allia Bay, Kenya: A multiproxy analysis of early Pliocene Bovidae. Issue 151 (February 2021) - Dumouchel, Laurence; Bobe, René; Wynn, Jonathan G.; Barr, W. Andrew
Abstract: Australopithecus anamensis, among the earliest fully bipedal hominin species, lived in eastern Africa around 4 Ma. Much of what is currently known about the paleoecology of A. anamensis comes from the type locality, Kanapoi, Kenya. Here, we extend knowledge of the range of environments occupied by A. anamensis by presenting the first multiproxy paleoecological analysis focusing on Bovidae excavated from another important locality where A. anamensis was recovered, locality 261-1 (ca . 3.97 Ma) at Allia Bay, East Turkana, Kenya. Paleoenvironments are reconstructed using astragalar ecomorphology, mesowear, hypsodonty index, and oxygen and carbon isotopes from dental enamel. We compare our results to those obtained from Kanapoi. Our results show that the bovid community composition is similar between the two fossil assemblages. Allia Bay and Kanapoi bovid astragalar ecomorphology spans the spectrum of modern morphologies indicative of grassland, woodland, and even forest-adapted forms. Dietary reconstructions based on stable isotopes, mesowear, and hypsodonty reveal that these bovids' diet encompassed the full C3 to C4 dietary spectrum and overlap in the two data sets. Our results allow us to confidently extend our reconstructions of the paleoenvironments of A. anamensis at Kanapoi to Allia Bay, where this pivotal hominin species is associated with heterogeneous settings including habitats with varying degrees of tree cover, including grasslands, bushlands, and woodlands. Highlights: Paleoenvironments at Allia Bay ca. 4 Ma were comparable with that of Kanapoi. Mixed feeders are common within bovids in the Allia Bay and Kanapoi assemblages. Australopithecus anamensis inhabited various habitats, including open grasslands.